Myanmar High School Students’ Perceptions of College and International Readiness in Western Society - Speckien, Mark; Ku, Heng-Yu (Journal of International Students, 2023)
The purpose of this study was to examine the perceptions of high school students associated with a United States-based preparatory school located in Myanmar regarding their readiness for college in Western society. In this two-stage study, quantitative data were collected using a 100-item 5-point Likert-scale survey focusing on college and international readiness completed by 49 participants, and qualitative data were gathered from 14 participants who participated in focus group interview sessions. Quantitative results yielded a mean of 3.42 (SD=1.08, N=49) for college readiness and a mean of 3.73 (SD=1.09, N=49) for international readiness. The qualitative findings showed the emergence of four themes: (a) mixed feelings on transitioning to independence, (b) concerns about adapting to a new culture, (c) lack of preparedness for college-level academics, and (d) unconcerned about making friends. These results indicated that the participants felt generally prepared to transition to a postsecondary setting in a Western country.